Cover Picture: Ann. Phys. 1‐2'2013. Issue 1 (8th February 2013) - Hommelhoff, Peter; Kling, Matthias; Stockman, Mark
<x xml:space="preserve">Abstract</x> Femtosecond electron switch. A laser pulse causes diffractive scattering of a synchronous electron pulse from a plasmonic structure. The electrons can interact through the ponderomotive potential and the instantaneous electric field of the near‐field enhanced laser pulse. Picture: M. Becker et al., 10.1002/andp.201200206, p. L6 in this issue <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>